2008
DOI: 10.3748/wjg.14.6453
|View full text |Cite
|
Sign up to set email alerts
|

Role of probiotics, prebiotics and synbiotics in chemoprevention for colorectal cancer

Abstract: Colorectal cancer is the third most common form of cancer. Current treatments are all associated with a high risk of complications and a low success rate. Recently, synbiotics have been proposed as a new preventive and therapeutic option. There is no direct experimental evidence for cancer suppression in humans as a result of the consumption of pro-, preor synbiotics. However, there is a wealth of evidence emerging from laboratory studies. The mechanisms by which pro-, pre-and synbiotics may inhibit colon canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 43 publications
6
81
0
4
Order By: Relevance
“…In vitro studies have demonstrated that lactic acid bacteria significantly reduce the growth and viability of the human colon cancer cell line HT-29 (39). An in vivo study in laboratory animals have additionally demonstrated that L. acidophilus and B. longum are able to reduce DNA damage and protect against 1,2-dimethylhydrazine-induced genotoxicity (40).…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies have demonstrated that lactic acid bacteria significantly reduce the growth and viability of the human colon cancer cell line HT-29 (39). An in vivo study in laboratory animals have additionally demonstrated that L. acidophilus and B. longum are able to reduce DNA damage and protect against 1,2-dimethylhydrazine-induced genotoxicity (40).…”
Section: Discussionmentioning
confidence: 98%
“…Propionibacterium freudenreichii was shown to induce cell death of human colon and gastric cancer cell lines through secretion of SCFAs in to culture media (Lee et al 2012). Bifidobacteria probiotics reduced colon carcinogenesis induced by 1, 2-dimethylhydrazine in mice when used with FOS and inhibited liver and mammary tumors in rats (Fotiadis et al 2008).…”
Section: Cardiovascular Diseases and Lipid Metabolismmentioning
confidence: 99%
“…Overall, studies in vitro systems and in a wide range of animal models provide considerable evidence that probiotics, prebiotics and synbiotics exert anti-neoplastic effects. (Fotiadis et al 2008).…”
Section: Cardiovascular Diseases and Lipid Metabolismmentioning
confidence: 99%
“…66 Providing probiotics with selective fermentable substrates that support their growth (i.e., synbiotics) has been found to produce greater health impacts than either alone. 67,68 Prebiotics such as nondigestible carbohydrates (e.g., galactooligosaccharides (GOS), fructo-oligosaccharides (FOS), resistant starch, polydextrose, and inulin), dietary fibers, and conjugated fatty acids have also been investigated for their role in IBD. 69 In a European study, SYNCAN, a probiotic mixture of Lactobacillus rhamnosus GG (LGG) and B. lactis Bbl2 along with the prebiotic oligofructose-enriched inulin was administered to patients who had undergone a polypectomy or been diagnosed with CRC.…”
Section: ■ Probiotics Prebiotics and Colon Cancermentioning
confidence: 99%